Wednesday

April 16, 2014

April 16, 2014

Posted by **log** on Thursday, July 2, 2009 at 7:49am.

given that

4^(2x+1) X 7^(x-1) = 8^x X 14^2x

evaluate 14^x

this is what i did, but i got stuck anyways.

2^(4x+2) X 7^(x-1) = 2^3x X 14^2x

2^(x+2) = 2^2x X 7^(x+1)

sorry this might be a bit confusing, but the big letter X is 'multiply'

- log -
**drwls**, Thursday, July 2, 2009 at 8:38am4^(2x+1) * 7^(x-1) = 8^x * 14^2x

4^2x * 4 * 7^x /7 = (4*2)^x * (7^x)^2

(4/7)*(4^x)^2 = 4^x * 2^x * 7^x

(4/7)* 4^x = 2^x * 7^x

(4/7)* (2*2)^x = 2^x * 7^x = (14^x)

(4/7)*2^x = 14^x = (2*7)^x

(4/7) = 7^x

x log 7 = log (4/7) = -.559616

x = -.28758

14^x = 0.46816

Check my thinking. There may be a mistake along the way.

I used base e log to get x, but the base doesn't matter in this case.

**Related Questions**

Algebra - I have a few questions that I am not too sure about, could you please ...

bobpursley,math - about this problem , I figured it out and i did get the answer...

Math - Can someone please check my answers below for accurateness? The ...

Algebra - Hello, can someone tell me if I got the following solve and check work...

math - last one on this topic i promise ;-) 4X-14+2X^3-7x^2 rearrange by degree ...

algebra1 - could you walk-through the steps to solving this problem because I am...

Quick math help - Can someone please check my math Hw? Thank you!! Solve each ...

Grade 10 Math - I've missed quite alot of school because I was sick and when I ...

math - Evaluate the following expressions for x=-3 13)–2x^2 = 14)(-2x)^2 = 10)...

math - Evaluate the following expressions for x=-3 13)–2x^2 = 14)(-2x)^2 = 10)...